Computational Simulation Techniques to Understand Rifampicin Resistance Mutation (S425L) of rpoB in M. leprae. Issue 7 (July 2015) - Nisha, J.; Shanthi, V.
ABSTRACT Mycobacterium leprae, the etiologic agent of leprosy, is non‐cultivable in vitro. Consequently, the assessment of antibiotic activity against M. leprae hinge mainly upon the time consuming mouse footpad system. As M. leprae develops resistance against most of the drugs, the evolution of new long acting antimycobacterial compounds stand in need for leprosy control. The rpoB of M. leprae is the target of antimycobacterial drug, rifampicin. Recently, cases were reported that rpoB mutation (S425L) became resistant to rifampicin and the mechanism of resistance is still not well understood. The present study is aimed at studying the molecular and structural mechanism of the rifampicin binding to both native and mutant rpoB through computational approaches. From molecular docking, we demonstrated the stable binding of rifampicin through two hydrogen bonding with His420 residue of native than with mutant rpoB where one hydrogen bonding was found with Ser406. The difference in binding energies observed in the docking study evidently signifies that rifampicin is less effective in the treatment of patients with S425L variant. Moreover, the molecular dynamics studies also highlight the stable binding of rifampicin with native than mutant (S425L) rpoB. J. Cell. Biochem. 116: 1278–1285, 2015. © 2015 Wiley Periodicals, Inc.